Synthesis and characterization of curcumin-loaded cellulose nanoparticles targeting bacterial quorum sensing and biofilms in foodborne bacteria - Zubair, Mohammad; Husain, Fohad Mabood; Siddiqui, Zahid Hameed; Khan Athar, Altaf; Alamri, Marai; Faisal Muhammad Ali Albudair, Shoug (Frontiers in Microbiology, 2026)
Over the past 25 years, antimicrobial resistance (AMR) has become a significant global health threat and a major cause of mortality. Foodborne diseases caused by drug-resistant bacteria capable of forming biofilms present serious health risks, necessitating innovative solutions for infectious disease management. Cellulose nanoparticles (CNPs), biocompatible and biodegradable, have found applications in targeted drug delivery, regenerative medicine, and tissue engineering. This study focuses on the synthesis and characterization of curcumin-loaded cellulose nanoparticles (CLCN) and their effects on quorum sensing (QS) and biofilm formation in both Gram-negative and Gram-positive foodborne bacteria (Escherichia coli, Pseudomonas aeruginosa, Serratia marcescens, Chromobacterium violaceum, and Listeria monocytogenes). FTIR confirmed molecular interactions between cellulose hydroxyl groups and curcumin. Thermal analysis (TGA/DSC) demonstrated enhanced structural stability with a gradual mass loss profile. Further, elemental composition analysis showed presence of carbon (50.6%) and oxygen (49.4%) in CLCN. CLCN exhibited MICs of 2 mg/mL against all test strains except in L. monocytogenes (8 mg/mL). At highest tested sub-MIC, violacein pigment was inhibited by over 58% in C. violaceum 12,472. CLCN disrupted pyocyanin, pyoverdin, LasB elastase, and rhamnolipid production by 53, 44, 39, and 47%, respectively. Exoprotease activity in test pathogens decreased by up to 58%. Biofilm production in all pathogens was significantly inhibited in the range of 48–68% at 0.5xMICs. Also, CLCN effectively removed preformed biofilms up to 46%. This study demonstrates that CLCN disrupt QS-regulated virulence traits and destabilizing biofilm architecture. By targeting virulence rather than growth, CLCN minimize the likelihood of resistance development and may serve as an adjunct or alternative to conventional antibiotic therapy. Thus, CLCN offer a biocompatible and sustainable antimicrobial strategy for food packaging systems, that limits surface-associated contamination and enhance food safety.